The impact of water pollution on the spread of (malaria) in the state of Gezira, Sudan - Mohammed, Amal Ibrahim (Journal of natural sciences, life and applied sciences, 2023)
The study described, analyzed and evaluated the impact of water pollution on the spread of malaria in two localities in the south of the island. The study aimed to achieve the following through research, investigation and analysis, highlighting the role of environmental factors and their impact on the spread of diseases in the study area. And to identify the relationship between the level of income and the spread of environmental diseases in the study area. And the study of the relationship between the type of food and the spread of diseases in the study area, in which the environment has a role. The study used the descriptive approach to provide a description of the natural and human phenomena related to the subject of the study, as well as the historical approach to describe and narrate the history of the phenomenon in the study community, and the analytical-statistical approach to achieve the objectives of the study. The most important findings of the study are the levelness levelrface of the region and the absence of rainwater drains. This led to the presence of water swamps, especially in the rainy season, which had a role in the breeding of mosquitoes and the spread of malaria, and this fulfills the first hypothesis. The low level of household income has an effect on the inability of the population to provide the necessary food with the required calories, which leads to a decrease in the level of immunity, which has an impact on the exposure of the population to diseases associated with malnutrition, especially children, and this is what achieves the second hypothesis. Since the study area is a rural agricultural area and the lack of health awareness and preservation of the environment helped in the spread of diseases related to environmental health, this is what achieves the fourth and fifth hypotheses. The study recommended paying attention to the environment and ridding it of carriers of pathogens such as mosquitoes, snails, flies, and others. This means paying attention to prevention, which is better than treatment and costs less. And the need to know the details of the factors that cause diseases, because this creates a state of disease prevention. Educating workers in various fields about occupational diseases that may be related to the nature of their work and the need to provide them with tools and means of prevention and safety during work.